A "bridge" over troubled water: Implications of the effect of locomotion mode on hopelessness. Issue 12 (17th September 2018) - Di Santo, Daniela; Baldner, Conrad; Pierro, Antonio; Kruglanski, Arie W.
Abstract: Past research has shown that hopelessness drastically reduces the quality of life. It follows that it could be particularly useful to improve our knowledge of the potential correlates of feelings of hopelessness. We propose a negative association between locomotion mode, or the self‐regulation dimension concerned with movement from current state to future states, and hopelessness. We suggest, in two studies that higher locomotion is related to less hopelessness and results in higher levels of psychological well‐being. In Study 1, we showed that locomotion was significantly and negatively related to hopelessness. In Study 2, we confirmed this result and also observed that the hopelessness experienced by locomotors partially mediated the positive relationship between locomotion orientation and psychological well‐being. Implications for future research are discussed.